Dynamics of value chain in climate resilient vegetable production practices - Ujjal Raj Acharya; Krishna Prasad Pant (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Climate resilient practices in farming is an integrated process that reduces risks in production and marketing. This study introduced an integrated package of climate resilient practices in vegetable farming to cope with climate change and related problems. The study that was carried out in Udayapur district of Nepal and it analyzed application of climate resilient practices in value chain of vegetable farming. The data were obtained from Himalica pilot project initiated by International Centre for Integrated Mountain Development (ICIMOD) which surveyed 300 vegetable farm households using a semi-structured questionnaire. In addition, a checklist was used for Focus Group Discussions (FGDs) with farmers' groups. The collected data were coded and entered into Microsoft Excel and descriptive statistics such as frequency, percentage and mean were calculated. For the analysis of costs, revenue and profitability, simple accounting method was used. The study shows that profit of farmers depends on the market type and farmers revenue increases when they sell their produce through farmers' co-operatives. Farmers need irrigation water, material supports, technology as well as organized farmers' group in order to increase the profit and to mitigate the risk from climate change and climate variability. The study found that climate resilient practices in vegetable value chain benefits farmers in terms of social, economic and environmental aspects.